2010
DOI: 10.4314/tdj.v16i1.62041
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and antenatal determinants of orofacial clefts in Benin City, Edo State Nigeria

Abstract: Aim: This study was undertaken to determine the prevalence and antenatal determinants of orofacial clefts in Southern Nigeria. Methods: A cross-sectional descriptive study undertaken at the Maxillofacial Units of the University of Benin Teaching Hospital and the Central Hospital, Benin City, Nigeria respectively. The prevalence and antenatal determinants of cleft lip and palate were determined. Result:Cleft lip and palate were often encountered in clinical practice in Benin City with a prevalence of 1.35%. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
5
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 23 publications
4
19
5
2
Order By: Relevance
“…The female preponderance of 63.6% recorded in this study is similar to the rate previously reported by Omo-Aghoja et al . [12] However, this is in contrast with earlier studies, which found no discernible difference in gender distribution of affected individuals. [1] The lip pits in VWS has been reported to be mostly bilateral and symmetrically placed on each side of the midline [1,5,13] and may sometimes be the only manifestation of this syndrome as seen in the mother of one of the presented case.…”
Section: Discussioncontrasting
confidence: 69%
“…The female preponderance of 63.6% recorded in this study is similar to the rate previously reported by Omo-Aghoja et al . [12] However, this is in contrast with earlier studies, which found no discernible difference in gender distribution of affected individuals. [1] The lip pits in VWS has been reported to be mostly bilateral and symmetrically placed on each side of the midline [1,5,13] and may sometimes be the only manifestation of this syndrome as seen in the mother of one of the presented case.…”
Section: Discussioncontrasting
confidence: 69%
“…Comme pour la plupart de malformations congénitales cardiaques, la prédominance masculine est à noter dans les FLP sans aucune explication fournie jusqu'à ce jour. Cependant, d'autres auteurs ont fait un constat différent : c'est le cas de Liluis [ 25 ] en Finlande, d'Omo-Aghoja [ 26 ] au sud du Nigéria et de Diombana [ 27 ] au Mali qui ont trouvé respectivement 50,6%, 51,5% et 53,8% des sujets féminins. Trente-cinq virgule sept pourcent de nos patients occupent la deuxième position dans la fratrie.…”
Section: Discussionunclassified
“…A l'instar d'Eshete [ 8 ], nous n'avons observé aucun cas de fente médiane. Signalons toute fois qu'Omo-Aghoja a trouvé une répartition égale des fentes unilatérales à gauche comme à droite [ 26 ]. L'étude rapporte 4,5% de malformations associées avec une prédominance des atteintes squelettiques (5 cas) puis cranio-faciales (1 cas) et cardiaques (1 cas).…”
Section: Discussionunclassified
“…[11] This index case was from a low socio economic class the veracity of use of herbal medications in pregnancy could not be determined; mother was in her early thirties while the father was in his late thirties.…”
Section: Discussionmentioning
confidence: 99%